Does preoperative magnetic resonance imaging alter the surgical plan in patients with acute traumatic cervical spinal cord injury?. Issue 1 (January 2021) - Buchanan, Frank R.; Wang, Vincent Y.; Amadio, Jordan P.; Ortega-Barnett, Juan R.; Brown, Lawrence H.; Teixeira, Pedro G.; Aydelotte, Jayson D.; Leede, Emily; Ali, Sadia; Brown, Carlos V.R.
Abstract : BACKGROUND: Whether magnetic resonance imaging (MRI) adds value to surgical planning for patients with acute traumatic cervical spinal cord injury (ATCSCI) remains controversial. In this study, we compared surgeons' operative planning decisions with and without preoperative MRI. We had two hypotheses: (1) the surgical plan for ATCSCI would not change substantially after the MRI and (2) intersurgeon agreement on the surgical plan would also not change substantially after the MRI. METHODS: We performed a vignette-based survey study that included a retrospective review of all adult trauma patients who presented to our American College of Surgeons-verified level 1 trauma center from 2010 to 2019 with signs of acute quadriplegia and underwent computed tomography (CT), MRI, and subsequent cervical spine surgery within 48 hours of admission. We abstracted patient demographics, admission physiology, and injury details. Patient clinical scenarios were presented to three spine surgeons, first with only the CT and then, a minimum of 2 weeks later, with both the CT and MRI. At each presentation, the surgeons identified their surgical plan, which included timing (none, <8, <24, >24 hours), approach (anterior, posterior, circumferential), and targeted vertebral levels. The outcomes were change in surgical plan and intersurgeon agreement. We used Fleiss' kappa ( κ ) to measure intersurgeon agreement. RESULTS: Twenty-nine patients met the criteria and were included. Ninety-three percent of the surgical plans were changed after the MRI. Intersurgeon agreement was "slight" to "fair" both before the MRI (timing, κ = 0.22; approach, κ = 0.35; levels, κ = 0.13) and after the MRI (timing, κ = 0.06; approach, κ = 0.27; levels, κ = 0.10). CONCLUSION: Surgical plans for ATCSCI changed substantially when the MRI was presented in addition to the CT; however, intersurgeon agreement regarding the surgical plan was low and not improved by the addition of the MRI. LEVEL OF EVIDENCE: Diagnostic, level II.